2023
DOI: 10.3390/jrfm16020128
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Financial Flow Model for the Sustainable Development of an Industrial Enterprise

Abstract: The review of modern methodological approaches to assessing the sustainable development of an industrial enterprise revealed the absence of generally accepted integral tools and the connection sustainable development trends with financial flows. To fill this gap this, taking into account the principle of balanced development economic, environmental and social components aimed. The purpose of the study is the development of a financial flow management model for the sustainable development of an industrial enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The link between "corporate sustainability" and "firm performance" has been a subject of extensive research and debate. Numerous studies have identified a positive correlation between corporate sustainability and the financial performance of firms (Galimulina et al 2023), suggesting that companies that prioritise sustainability practices tend to outperform their competitors (Ioannou and Serafeim 2019; Ammer et al 2020). This can be attributed to several factors, including cost savings through energy efficiency and waste reduction, enhanced brand reputation and customer loyalty, increased employee engagement and productivity, and improved risk management (Rodgers et al 2019).…”
Section: Corporate Sustainability and Firm Performance Relationshipmentioning
confidence: 99%
“…The link between "corporate sustainability" and "firm performance" has been a subject of extensive research and debate. Numerous studies have identified a positive correlation between corporate sustainability and the financial performance of firms (Galimulina et al 2023), suggesting that companies that prioritise sustainability practices tend to outperform their competitors (Ioannou and Serafeim 2019; Ammer et al 2020). This can be attributed to several factors, including cost savings through energy efficiency and waste reduction, enhanced brand reputation and customer loyalty, increased employee engagement and productivity, and improved risk management (Rodgers et al 2019).…”
Section: Corporate Sustainability and Firm Performance Relationshipmentioning
confidence: 99%